De l’Océanie divisée à l’Océanie unifiée par la mer. En mémoire de Epeli Hau‘ofa - Serge Tcherkézoff (Archivio Antropologico Mediterraneo)
Oceania, shortly after being invented by European geographers as the «fifth» region of the world, in other words simply a ‘remnant’ after the four continents, was divided into watertight compartments as a result of the privilege given in the early 19th century to the theory of human ‘races’ in the world. It was not until 1993 that a declaration, now celebrated as historic, by an Oceanian teacher and writer, Epeli Hau‘ofa, proclaimed the unity of Oceania by the very fact of being an “oceanic” region. This development, the discussion of the terms “Pacific”/“Oceania”, and the historical legacy today will be recalled, as well as an evocation of the life and work of Epeli Hau'ofa. Finally, the comparison between two different visions of the continent (d'Urville and Hau'ofa) will allow us to reflect on the different interpretations and representations of the sea and the ocean as spaces that in one case divide and, in the other, unite.